Structure-specific antitumor effects and potential gut microbiota-involved mechanisms of ginseng polysaccharides on B16F10 melanoma-bearing mice. Issue 2 (6th January 2023) - Xie, Ni-Na; Wu, Cheng-Ying; Ge, Qiong; Zhou, Jing; Long, Fang; Mao, Qian; Li, Song-Lin; Shen, Hong
Abstract : GP-n contribute to the anti-melanoma effects of GP-c, and the potential mechanisms might be related with its structure, specifically the upregulation of Allobaculum and Bifidobacterium and SCFAs levels, such as acetic acid and butyric acid. Abstract : Ginseng polysaccharides (GPs) have shown gut microbiota-related antitumor effects. However, the relation between their structures and antitumor functions remains unknown. Here, crude polysaccharide (GP-c) and its fractions neutral polysaccharide (GP-n) and pectin (GP-a) were prepared for structure characterization and anti-B16F10 melanoma effect evaluation, and their influence on gut microbiota diversities and short-chain fatty acids (SCFAs) were also analyzed. Spearman correlations among the altered gut microbiota, SCFAs, and antitumor effects were conducted to elucidate the structure–function relationships. It was shown that the structures of GP-c, GP-n, and GP-a varied in monosaccharide composition and molecular weight distribution. GP-n and GP-c showed anti-melanoma effects, whereas GP-a promoted its growth slightly. GP-n and GP-c restored SCFAs levels such as acetic acid and butyric acid; moreover, it improved the gut microbiota ecosystem by upregulating the abundance of Allobaculum and Bifidobacterium . However, the restoration effect of GP-a was weak, or even worse. In addition, these two bacteria were negatively correlated with the tumor weight and related with the altered SCFAs. In conclusion, GP-n is essential for the anti-melanoma effects of GP, and the potential mechanisms might be related with its specific regulation of Allobaculum and Bifidobacterium abundance, and tumor-associated SCFAs levels. The outcomes highlighted here enable a deeper insight into the structure–function relationship of GP and propose new opinions on its antitumor effect.